Evaluation of effectiveness of resource-saving technologies in machine-building industry - S. S. Kudryavtseva; M. V. Shinkevich (Омский научный вестник)
The article analyzes the effectiveness of the use of resource-saving technologies in machine-building complex. With the transition of production and business systems to work in the context of the formation of the sixth technological order, issues of increasing the efficiency of production processes acquire special significance and relevance. The purpose of the article is to summarize the main trends in the implementation of resource-saving technologies at the enterprises of the machine-building complex of the economy and the development of a mathematical model to assess the effectiveness of the use of resource-saving systems. The presented results of the study are of great economic importance not only for the machine-building complex as a whole, but can also be used by individual enterprises in the real sector of the economy to assess the level of effectiveness of implemented and used resource-saving technologies expressed through the increase in added value.